Paisagem cultural da cidade de Goiás: representações de moradores e visitantes - Magalhães Filho, Fernando Silva (2014)
The city of Goiás, the old Vila Boa, was one of the first urban center of the Brazilian midwest, due to gold mining exploration in the eighteenth century and also the capital of Goiás state until 1937. It is an example of Portuguese occupation in the Brazilian backlands, its vernacular architecture of baroque inspiration it is today globally recognized by the title of Cultural Heritage of Humanity by Unesco in 2001. The international importance of its historical collection made it dynamic with the increase in tourism activity. The city which, hitherto, tasted a bitter low economic development since the transference of the capital to Goiânia, saw the tourism as a socio-economic revitalization of vilaboense society. The world exposure makes Goiás begins to welcome tourists from other states and even from other countries, leading to changes in the socio-economic and spatial structures in the city. One of the main actions developed was the intensification of heritage policies, aiming at enhancing the cultural heritage of the city, that (re)create new landscapes of Goiás. In this context, we developed this study in order to understand how the seizure of the cultural landscape of Goiás by spatial representation of locals and tourists by the application of mental maps and questionaries. The qualitative research approach was based on a theoretical discussion about the categories, heritage and landscape, in addition to prominent concepts related to spatial representation and tourism. For the interpretation of mental maps, we used the Kozel methodology (2001). The found results show the interfaces between the views of residents and visitors about the cultural landscape and how the methodology can contribute to more participatory heritage polices, based on studies of landscapes.